Asymptomatic Bacteriuria (ASB) in Pregnancy: Prevalence and Fetal Risk - Farkhunda Khursheed, Chandra Madhudas, Saima Ghaffar, Bhawna, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the prevalence of Asymptomatic Bacteriuria (ASB) and its association with fetal outcome at tertiary care Hospital. Material and Methods: This was a descriptive cross-sectional study was conducted at the Obstetrics and Gynaecology department of Liaquat University of Medical and Health Sciences for six months from February 2021 to August 2021. Total 2838 pregnant women in third trimester (more than 28 weeks of gestion) whose urine sample were taken, aged 18 to 41 years of either parity or booking status were included. Following the clinical examination, the investigator gave each mother a labeled sterile container and instructed them about how to obtain midstream urine, after that the urine samples were obtained and were sent to the Hospital diagnostic laboratory for the urine culture. A positive culture of each case was considered Asymptomatic Bacteriuria (ASB). All the data were gathered using the self-made study proforma. SPSS version 26 was used to analyze the data. Results: Total 2838 women were assessed regarding Asymptomatic Bacteriuria (ASB), and the overall incidence of Asymptomatic Bacteriuria (ASB) was (5.32%). Mean age of the women was 27.70+4.83 years and the average gestational age was 37.11+2.91 weeks. Most of the females were primiparous 90(59.6%). Majority of the cases 93(61.6%) were un-booked. As per fetal complications 31(20.5%) new born were low birth weight babies, PROM was 22(14.6%) and preterm deliveries were 28(18.5%). Fetal complications were statistically significant according to maternal age and gestational age (p-<0.05), while they were statistically insignificant according to parity and booking status (p-.0.05). Conclusion: Asymptomatic Bacteriuria (ASB) was observed to be 5.32%. Asymptomatic Bacteriuria (ASB) observed to be the causative factor for adverse fetal outcome. Urine culture should be done during the antenatal care to improve the fetal outcome by early diagnosis and management.